Sustainable business – a success story for small and medium sized enterprises? - Dirk Drenk (European Regional Science Association (ERSA), 2005)
In the last years not only large companies orientated themselves towards the goal of sustainable development - which is called sustainable business in the economic field. More and more small and medium sized enterprises (SME's) discovered the field of sustainable business hoping to achieve economic advantages compared to their competitors. In order to become a company according to the principles of sustainable business, many businesses in Germany applied for an "ÖKOPROFIT”-certification. The aim of this paper is to present the results of a survey of small and medium sized enterprises who achieved the ÖKOPROFIT-certification in the last four years. Questions that will be answered are for instance if these companies created more jobs than their competitors, or if the SME's gained a better image by their costumers and purchasers. Furthermore it is intended to answer the question whether the ÖKOPROFIT-certification and of course sustainable business have an impact on the economic development of the companies or if cyclical trends overlay these effects.
Keywords: 330